STRUCTURE FORMATION OF HYPOEUTECTOID CONSTRUCTIONS STEELS AT CARBONITRIDING WITH LOCAL INDUCTION CYCLIC HEATING - G. A. Tkachenko (Литьë и металлургия, 2010)
Improvement of mechanical characteristics of details of the soil-cultivating car. Structurization at cyclic heating of steels. The reasons of an intensification of diffusion at cyclic heating. Structure crushing, impact strength and hardness increase.